Laminated film roll and method for manufacturing laminated film roll
By adopting specific laminated film structure and process conditions in the resin sheet, the problem of taking into account high smoothness and sliding properties of the resin sheet is solved, and efficient improvement of optical and electronic components is achieved.
Patent Information
- Application Number
- CN202380053830.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-07-18
AI Technical Summary
The prior art is difficult to take into account both high smoothness and good sliding properties in resin sheets, resulting in insufficient transparency, winding misalignment and reduced yield in optical and electronic components.
A laminated film roll with a polyester-based substrate film, a mold release layer and a resin sheet is used. The resin sheet is composed of a resin component (A) and a crosslinking agent (B). The composition is formed by curing through specific process conditions to ensure high smoothness and slipibility of the resin sheet.
High smoothness and good sliding properties of the resin sheet are achieved, problems of increased internal haze and uneven particles are avoided, and the performance of optical and electronic components is improved.
Smart Images

Figure CN119562893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated film roll on which a resin sheet is laminated, and particularly to a laminated film roll on which a resin sheet used for electronic components or optical applications is laminated. Background Art
[0002] In the past, release films using polyester films as substrates had high heat resistance and mechanical properties and were used as engineering films for solution film formation of resin sheets such as adhesive sheets, protective films, polymer electrolyte membranes, and dielectric resin sheets. In recent years, especially for electronic components such as dielectric resin sheets used in film capacitors and resin sheets used for optical purposes, high smoothness and transparency are required, and therefore, the surface of release films used as engineering films is also required to have high smoothness. Therefore, the technologies described in Patent Documents 1 to 3 are disclosed, and a scheme for reducing the surface roughness of the release layer surface is proposed.
[0003] However, for example, in optical applications, high smoothness is required to improve transparency, but on the other hand, high smoothness deteriorates the sliding property, and there is a concern that scratches may be caused during the conveying process, and the yield rate may be reduced. In addition, in electronic component applications such as film capacitor applications, smoothness is required to improve electrical properties such as dielectric breakdown voltage, but on the other hand, if the smoothness is too high, the sliding property is poor, and when the dielectric resin sheet is wound on a roll, winding misalignment and wrinkles may be mixed in, and it may not be wound well, and there is a concern that the performance of the film capacitor may be reduced.
[0004] In order to improve these, Patent Document 4 proposes adding specific particles to a resin sheet for optical use such as polarizing plates to impart slip properties. In addition, Patent Document 5 proposes a method of transferring particles on a substrate film to a resin sheet used in a film for a film capacitor or the like.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-144021
[0008] Patent Document 2: Japanese Patent Application Publication No. 2014-154273
[0009] Patent Document 3: Japanese Patent Application Publication No. 2015-182261
[0010] Patent Document 4: Japanese Patent Application Publication No. 2019-95661
[0011] Patent Document 5: International Publication No. 2020 / 039638 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] However, in the method of Patent Document 4, since the particles are contained in the resin sheet, there is a concern that the transparency may be insufficient, such as an increase in internal haze. In addition, in the method of Patent Document 5, there is a concern that the amount of particles transferred to the resin sheet may become uneven, and there is a concern that the sliding property may become unstable.
[0014] The present invention is to solve the above-mentioned problems and proposes a laminated film roll that can provide a resin sheet having both high smoothness and good sliding properties without substantially adding particles inside the resin sheet.
[0015] Solutions for solving problems
[0016] The inventors of the present invention have conducted intensive research and found that in a laminated film roll comprising a polyester-based substrate film, a release layer disposed on at least one side of the aforementioned substrate film, and a resin sheet disposed on the side of the aforementioned release layer opposite to the substrate, the above-mentioned problem can be solved by making the resin sheet have the technical features described in this specification.
[0017] That is, the present invention includes the following configurations.
[0018] [1] A laminated film roll comprising: a polyester-based base film, a release layer disposed on at least one surface of the base film, and a resin sheet disposed on a surface of the release layer opposite to the base film,
[0019] The laminated film roll meets the following conditions:
[0020] The resin sheet is obtained by curing a resin sheet-forming composition containing at least a resin component (A) and a crosslinking agent (B).
[0021] The resin sheet contains virtually no particles.
[0022] The film thickness (t1) of the resin sheet is 1 μm or more and 20 μm or less,
[0023] The arithmetic mean height (Sa) of the surface (1) of the resin sheet opposite to the release layer is 2 nm or more and 30 nm or less,
[0024] The maximum cross-sectional height (St) of the surface (1) of the resin sheet opposite to the release layer is 80 nm or more and 1000 nm or less,
[0025] The static friction coefficient measured by overlapping the surface (1) of the resin sheet opposite to the release layer and the surface (2) of the resin sheet on the release layer side is 1.5 or less.
[0026] The roll hardness of the surface of the laminated film roll is 900 or less.
[0027] [2] The laminated film roll according to [1], wherein the crosslinking agent (B) contained in the resin sheet forming composition is liquid at 30°C.
[0028] [3] The laminated film roll according to [1] or [2], wherein the ratio of the crosslinking agent (B) contained in the resin sheet to the entire resin sheet is 10% by mass or more, when the total solid content of the resin sheet is 100% by mass.
[0029] [4] The laminated film roll according to any one of [1] to [3] above, wherein the weight average molecular weight of the resin component (A) contained in the resin sheet is 10,000 or more.
[0030] [5] The laminated film roll according to any one of [1] to [4], wherein the surface free energy of the release layer surface is 40 mJ / m 2 Below, and water adhesion energy is 3.0mJ / m 2 above.
[0031] [6] The laminated film roll according to any one of [1] to [5], wherein the arithmetic mean height (Sa) of the release layer side surface of the base film is 20 nm or less, and the maximum protrusion height (P) is 500 nm or less.
[0032] [7] In another aspect, the present invention provides the following production method.
[0033] A method for producing a laminated film roll, characterized in that it is the method for producing a laminated film roll according to any one of [1] to [6] above, wherein the resin sheet is applied to the release layer by a solution film forming method and then molded.
[0034] Effects of the Invention
[0035] By using the laminated film roll of the present invention, a resin sheet having both high smoothness and good sliding properties can be provided, and by using the resin sheet molded in the present invention, good products can be provided in various applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic cross-sectional view showing the structure of the present invention.
[0037] Figure 2 This is a schematic cross-sectional view for explaining the structure of the present invention in one embodiment. DETAILED DESCRIPTION
[0038] The inventors of the present application have found that a release layer is provided on a smooth substrate film, a resin sheet-forming composition containing at least a specific resin and a cross-linking agent is applied under the conditions described in the present specification, and then dried / cured to obtain a resin sheet of the present invention. The inventors of the present application have further found that by rolling up the laminated body obtained under the conditions described in the present specification, unevenness due to a phase separation structure is formed on the surface of the laminated film, and the laminated film roll is successfully made to have good sliding properties without containing particles.
[0039] In the present invention, the resin sheet can have high smoothness and sliding properties in a well-balanced manner, for example, it is possible to suppress the reduction in yield that may occur in the conveying process. In addition, in the case where the resin sheet can be used for electronic components such as film capacitors, the present invention can have high smoothness and sliding properties in a well-balanced manner, thereby improving electrical properties such as dielectric breakdown voltage. In addition, in the present invention, when the dielectric resin sheet is wound on a roller, the mixing of winding misalignment and wrinkles can be suppressed, and a good roll can be obtained. Therefore, for example, it becomes easy to control the performance of the film capacitor as designed.
[0040] In addition, in the present invention, since the resin sheet does not substantially contain particles, it is also possible to suppress the particles from slipping during the production process, and to obtain a resin sheet with higher precision, such as a dielectric resin sheet or a film capacitor.
[0041] The present invention is a laminated film roll, comprising: a polyester-based substrate film, a release layer disposed on at least one surface of the substrate film, and a resin sheet disposed on a surface of the release layer opposite to the substrate, wherein the laminated film roll satisfies the following conditions:
[0042] The resin sheet is obtained by curing a resin sheet-forming composition containing at least a resin component (A) and a crosslinking agent (B).
[0043] The resin sheet contains virtually no particles.
[0044] The film thickness (t1) of the resin sheet is 1 μm or more and 20 μm or less,
[0045] The arithmetic mean height (Sa) of the surface (1) of the resin sheet opposite to the release layer is 2 nm or more and 30 nm or less,
[0046] The maximum cross-sectional height (St) of the surface (1) of the resin sheet opposite to the release layer is 80 nm or more and 1000 nm or less,
[0047] The static friction coefficient measured by overlapping the surface (1) of the resin sheet opposite to the release layer and the surface (2) of the resin sheet on the release layer side is 1.5 or less.
[0048] The roll hardness of the surface of the laminated film roll is 900 or less.
[0049] The laminated film roll of the present invention having such characteristics is as follows Figure 1 As shown, a laminate film is wound into a roll, wherein the laminate film has a polyester-based base film 10, a release layer 11 disposed on at least one side of the base film 10, and a resin sheet 12 disposed on the side of the release layer 11 opposite to the base film 10.
[0050] In the present invention, the state in which the laminated film is rolled up is a state in which the surface of the resin sheet 12 opposite to the release layer 11 is in contact with the surface of the base film 10 opposite to the release layer 11 and is rolled up.
[0051] The laminated film roll includes, for example, a polyester-based base film, a release layer, and a resin sheet in this order.
[0052] The present invention can provide, for example, a resin sheet that can improve transparency in optical applications, and a resin sheet that exhibits high smoothness. In addition, it is possible to combine high smoothness and high sliding properties that were previously difficult to achieve, for example, to suppress scratches during the conveying process, and to avoid a reduction in the yield rate.
[0053] In addition, it is possible to provide a resin sheet that exhibits high smoothness for electronic component applications such as film capacitor applications, and the resin sheet can improve electrical properties such as dielectric breakdown voltage. In addition, it is possible to achieve both high smoothness and high sliding properties that were previously difficult to achieve, such as suppressing winding misalignment and wrinkles when winding a dielectric resin sheet on a roll, and exhibiting good winding properties. Therefore, it is possible to transport the sheet while maintaining excellent capacitor performance.
[0054] Furthermore, in the present invention, the resin sheet contains substantially no particles, and insufficient transparency due to increased internal haze can be avoided. In addition, the problem of uneven amount of particles transferred to the resin sheet can be avoided, and good sliding properties can be exhibited.
[0055] (Base film)
[0056] The present invention has a polyester-based substrate film. The polyester constituting the polyester film used as the substrate of the present invention is not particularly limited, and a film formed from a polyester generally used as a substrate film can be used. Preferably, a crystalline linear saturated polyester containing an aromatic dibasic acid component and a diol component is used, and for example, polyethylene terephthalate, polyethylene naphthalate-2,6-ethylene glycol ester, polybutylene terephthalate, polytrimethylene terephthalate, or a copolymer having the constituent components of these resins as the main component is more suitable. In particular, a polyester film formed from polyethylene terephthalate is particularly suitable.
[0057] The repeating unit of ethylene terephthalate in polyethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and may be copolymerized with a small amount of other dicarboxylic acid components and glycol components. From the aspect of cost, it is preferred to be made only of terephthalic acid and ethylene glycol. In addition, within the scope that does not hinder the effect of the film of the present invention, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may also be added. For reasons such as the height of the elastic modulus in both directions, the polyester film is preferably a biaxially oriented polyester film.
[0058] The intrinsic viscosity of the polyethylene terephthalate film is preferably 0.50 to 0.70 dl / g, more preferably 0.52 to 0.62 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, it is not preferred because it frequently breaks during the stretching process. On the contrary, when it is 0.70 dl / g or less, it is preferred because it has good cutting properties when cut into a predetermined product width and does not cause dimensional defects. In addition, the raw material pellets are preferably fully vacuum dried.
[0059] The method for producing the polyester film of the present invention is not particularly limited, and a conventionally used method can be used. For example, the polyester is melted in an extruder, extruded into a film, cooled on a rotating cooling drum, thereby obtaining an unstretched film, and the unstretched film is stretched to obtain the polyester film. For mechanical properties, etc., the stretching is preferably biaxial stretching. The biaxially stretched film can be obtained by a method of sequentially biaxially stretching a uniaxially stretched film in the longitudinal or transverse direction in the transverse direction or in the longitudinal direction, or by a method of simultaneously biaxially stretching an unstretched film in the longitudinal and transverse directions.
[0060] In the present invention, the stretching temperature during stretching of the polyester film is preferably set to be equal to or higher than the secondary transition point (Tg) of the polyester. The film is preferably stretched 1 to 8 times, particularly preferably 2 to 6 times, in each of the longitudinal and transverse directions.
[0061] The polyester film preferably has a thickness of 6 μm or more and 50 μm or less, more preferably 8 μm or more and 31 μm or less, and more preferably 10 μm or more and 28 μm or less. If the thickness of the film is 6 μm or more, it is preferred that there is no concern about thermal deformation during film production, the processing steps of the release layer, and the molding of the resin sheet. On the other hand, if the thickness of the film is 50 μm or less, the roll diameter when wound into a roll is small, and the roll length of the molded resin sheet can be extended, so it is preferred.
[0062] When the polyester film as the base film has a multilayer structure described below, the film thickness of the base film as a whole falls within the above range.
[0063] The polyester film may be a single layer or a multilayer of more than two layers. It is preferred that at least one side has a surface layer A substantially free of particles. In one embodiment, the polyester film as the substrate film has a surface layer A on one side of the resin sheet. In the case where the substrate film is a laminated polyester film having a multilayer structure of more than two layers, it is preferred that the surface layer B that may contain particles is provided on the opposite side of the surface layer A substantially free of particles. As a laminated structure, when the layer on one side of the resin sheet is configured as the surface layer A, the layer on the opposite side is configured as the surface layer B, and the core layer other than these is configured as the layer C, a laminated structure such as A / B or A / C / B in the thickness direction can be cited.
[0064] Layer C may be composed of multiple layers. In addition, the surface layer B may not contain particles. In this case, in order to impart slidability for winding the film into a roll, it is preferred to provide a coating layer containing particles and a binder on the surface layer B.
[0065] In the polyester film of the present invention, the surface layer A located on the surface where the resin sheet is molded is preferably substantially free of particles. In addition, the arithmetic mean height (Sa) of the surface layer A of the polyester film, that is, the arithmetic mean height (Sa) of the release layer side surface of the substrate film is preferably less than 20nm. Further, the arithmetic mean height (Sa) is particularly preferably less than 10nm. If Sa is less than 20nm, it is not easy to cause pinholes and local uneven thickness during resin sheet molding and is preferred. It can be said that the smaller the arithmetic mean height (Sa) of the surface layer A, the more preferred, but it can also be more than 0.1nm. Here, in the case of setting the release layer described later on the surface layer A, it is preferred that the release layer is substantially free of particles, and the arithmetic mean height (Sa) after the release layer is stacked preferably falls within the aforementioned range. In the present invention, "substantially free of particles" means: for example, in the case of inorganic particles, when the inorganic elements are quantified by fluorescent X-ray analysis, the content becomes less than 50ppm, preferably less than 10ppm, and most preferably less than the detection limit. This is because even if particles are not actively added to the film, contamination components from foreign matter, raw resin or dirt attached to pipes and equipment in the film manufacturing process may be peeled off and mixed into the film. This definition can also be used for the technical feature of the present invention that "the resin sheet does not substantially contain particles".
[0066] The maximum protrusion height (P) of the surface layer A of the polyester film, that is, the maximum protrusion height (P) of the release layer side surface of the substrate film is, for example, 500 nm or less, preferably 200 nm or less, more preferably 150 nm or less, further preferably 100 nm or less, for example 85 nm or less, particularly preferably 50 nm or less. If the maximum protrusion height (P) is 500 nm or less, pinholes and local thinning and other bad spots will not be generated when the resin sheet is formed, and the yield is good and preferred.
[0067] The smaller the P of the surface layer A of the polyester film, the better, but it can be 1 nm or more, and can be 3 nm or more. Here, when a release layer described later is provided on the surface layer A, the maximum protrusion height (P) after lamination of the release layer preferably falls within the above range.
[0068] In the polyester film of the present invention, from the viewpoint of the slipperiness of the film and the ease of removing air, the surface layer B forming the opposite side of the surface layer A preferably contains particles, and it is particularly preferred to use silica particles and / or calcium carbonate particles. The particle content contained in the surface layer B preferably contains 5000 to 15000 ppm in total of particles. At this time, the arithmetic mean height (Sa) of the film of the surface layer B is preferably in the range of 1 to 40 nm. More preferably, it is in the range of 5 to 35 nm. When the total amount of silica particles and / or calcium carbonate particles is more than 5000 ppm and Sa is more than 1 nm, when the film is rolled up into a roll, air can be evenly detached, the winding morphology is good and the planarity is good, and it becomes suitable for manufacturing resin sheets. In addition, when the total amount of silica particles and / or calcium carbonate particles is less than 15000 ppm and Sa is less than 40 nm, it is not easy for lubricant to aggregate and no coarse protrusions are formed, so the quality is stable and preferred during the molding of the resin sheet.
[0069] As the particles contained in the above-mentioned surface layer B, inactive inorganic particles and / or heat-resistant organic particles can be used except silicon dioxide and / or calcium carbonate. From the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are more preferably used, but as inorganic particles that can be used in addition, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles, etc. can be cited. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be cited. In addition, when using silicon dioxide particles, porous colloidal silica is preferred, and when using calcium carbonate particles, from the viewpoint of preventing the lubricant from falling off, preferably a light calcium carbonate having been surface-treated with a polymer compound of a polyacrylic acid system.
[0070] The average particle size of the particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the particles is 0.1 μm or more, the slipperiness of the substrate film is good and it is preferred. In addition, if the average particle size is 2.0 μm or less, there is no concern about the generation of pinholes in the resin sheet caused by the coarse particles of the surface layer B and it is preferred.
[0071] The surface layer B may contain two or more particles made of different materials. Alternatively, the surface layer B may contain particles of the same kind but with different average particle sizes.
[0072] When the surface layer B does not contain particles, it is preferred that the surface layer B has lubricity by a coating containing particles. The coating is not particularly limited, and is preferably provided by an in-line coating applied during film formation of a polyester film. When the surface layer B does not contain particles and the surface layer B has a coating containing particles, the arithmetic mean height (Sa) of the surface of the coating is preferably in the range of 1 to 40 nm for the same reasons as the arithmetic mean height (Sa) of the surface layer B described above. More preferably, it is in the range of 5 to 35 nm.
[0073] In the surface layer A which is the layer provided on the resin sheet side, it is preferred not to use recycled raw materials or the like in order to prevent the mixing of particles such as lubricants from the viewpoint of reducing pinholes.
[0074] The thickness ratio of the layer on one side of the resin sheet, i.e., the surface layer A, is preferably 20% or more and 50% or less of the total layer thickness of the substrate film. If it is 20% or more, it is not easy to be affected by the particles contained in the surface layer B, etc. from the inside of the film, and the arithmetic mean height (Sa) is easy to meet the above range and is preferred. If it is 50% or less of the total layer thickness of the substrate film, the use ratio of the recycled raw materials in the surface layer B can be increased, and the environmental load becomes smaller and is preferred.
[0075] In addition, from the viewpoint of economic efficiency, 50 to 90% by mass of film scraps or recycled raw materials of plastic bottles can be used in the layer other than the surface layer A (surface layer B or the aforementioned intermediate layer C). In this case, it is also preferred that the type, amount, particle size and arithmetic mean height (Sa) of the lubricant contained in the surface layer B meet the above range.
[0076] In addition, in order to improve the adhesion of the release layer etc. applied later or to prevent electrostatic charge etc., a coating may be provided on the surface of the surface layer A and / or the surface layer B before stretching in the film-making process or on the film after uniaxial stretching, or a corona treatment etc. may be implemented. When a coating is provided on the surface layer A, the coating preferably does not contain particles substantially.
[0077] (Release layer)
[0078] The present invention has a release layer disposed on at least one side of the substrate film, for example, a release layer is provided between the substrate film and the resin sheet. The resin constituting the release layer is not particularly limited, and silicone resins, fluororesins, alkyd resins, various waxes, aliphatic olefins, etc. can be used, and each resin can be used alone or in combination of two or more. When a crosslinking agent is included in the resin sheet described later, it is preferred that the silicone resin is included because the release property becomes better.
[0079] In addition, in this specification, the laminated body of a base material and a release layer may be simply called a release film.
[0080] The release layer may include, for example, a silicone resin. A silicone resin is a resin having a silicone structure in the molecule, and examples thereof include curable silicone, silicone grafted resin, alkyl-modified modified silicone resins, etc. However, from the viewpoint of transferability, etc., it is preferred to use a reactive curable silicone resin. As a reactive curable silicone resin, an addition reaction system, a condensation reaction system, an ultraviolet or electron beam curing system, etc. may be used. More preferably, an addition reaction system of low-temperature curability that can be processed at low temperatures, and an ultraviolet or electron beam curing system may be used. By using these, when the polyester film is coated, it can be processed at low temperatures. Therefore, a polyester film with less thermal damage to the polyester film during processing and high flatness is obtained, and bad spots such as pinholes can also be reduced when manufacturing the resin sheet of the film.
[0081] Examples of the silicone resin of the addition reaction system include polydimethylsiloxane having a vinyl group introduced at the terminal or side chain and hydrogen siloxane reacted and cured using a platinum catalyst. In this case, it is more preferable to use a resin that can be cured within 30 seconds at 120° C. because processing at low temperatures is possible. As examples, there can be cited low-temperature addition curing types (LTC1006L, LTC1056L, LTC300B, LTC303E, LTC310, LTC314, LTC350G, LTC450A, LTC371G, LTC750A, LTC755, LTC760A, etc.) and thermal UV curing types (LTC851, BY24-510, BY24-561, BY24-562, etc.) manufactured by DowToray Co., Ltd., solvent addition + UV curing types (X62-5040, X62-5065, X62-5072T, KS5508, etc.), and Dual-cure curing types (X62-2835, X62-2834, X62-1980, etc.) manufactured by Shin-Etsu Chemical Co., Ltd.
[0082] Examples of the condensation reaction system silicone resin include silicone resins formed by condensing polydimethylsiloxane having an OH group at a terminal and polydimethylsiloxane having an H group at a terminal using an organic tin catalyst to form a three-dimensional crosslinked structure.
[0083] As UV-curable silicone resins, for example, there are: those that utilize the same free radical reaction as the most basic type of conventional silicone rubber cross-linking; those that introduce unsaturated groups and perform photocuring; those that decompose onium salts under ultraviolet light to generate strong acids, thereby cleaving epoxy groups and cross-linking; those that are cross-linked by the addition reaction of thiols to vinyl siloxane, etc. In addition, electron beams can also be used instead of the aforementioned ultraviolet rays. Electron beams have stronger energy than ultraviolet rays, and in the case of ultraviolet curing, free radical-based cross-linking reactions can be performed even without the use of initiators. Examples of the resin used include UV-curing silicones manufactured by Shin-Etsu Chemical Co., Ltd. (X62-7028A / B, X62-7052, X62-7205, X62-7622, X62-7629, X62-7660, etc.), UV-curing silicones manufactured by MOMENTIVE PERFORMANCE MATERIALS KK (TPR6502, TPR6501, TPR6500, UV9300, UV9315, XS56-A2982, UV9430, etc.), and UV-curing silicones manufactured by Arakawa Chemical Industries, Ltd. (SILCOLEASE UV POLY200, POLY215, POLY201, KF-UV265AM, etc.).
[0084] As the above-mentioned ultraviolet curing silicone resin, acrylate-modified, glycidoxy-modified polydimethylsiloxane, etc. can also be used. When these modified polydimethylsiloxanes are mixed with multifunctional acrylate resins, epoxy resins, etc. and used in the presence of an initiator, good mold release performance can also be demonstrated.
[0085] Examples of the resin used in addition include stearyl-modified, lauryl-modified, or other alkyd resins, acrylic resins, or alkyd resins, acrylic resins, and olefin resins obtained by reaction with methylated melamine.
[0086] Examples of the aminoalkyd resin obtained by reaction of methylated melamine include Tesfine 303, Tesfine 305, and Tesfine 314 manufactured by Hitachi Chemical Co., Ltd. Examples of the aminoacrylic resin obtained by reaction of methylated melamine include Tesfine 322 manufactured by Hitachi Chemical Co., Ltd.
[0087] When the above resins are used in the release layer of the present invention, they may be used alone or in combination of two or more. In order to adjust the release force, additives such as a light release additive and a heavy release additive may be mixed.
[0088] The release layer of the present invention may also contain additives such as adhesion improvers and antistatic agents. In addition, in order to improve adhesion with the substrate, it is also preferred to pre-treat the polyester film surface by anchor coating, corona treatment, plasma treatment, atmospheric pressure plasma treatment, etc. before providing the release layer.
[0089] In the present invention, the thickness of the release layer can be set according to its purpose of use without particular limitation, and the thickness of the release layer after curing is preferably in the range of 0.005 to 2.0 μm. If the thickness of the release layer is 0.005 μm or more, the peeling performance is maintained and it is preferred. In addition, if the thickness of the release layer is 2.0 μm or less, the curing time is not excessively prolonged, and there is no concern about uneven thickness of the resin sheet due to reduced planarity of the release film, which is preferred. In addition, the curing time is not excessively prolonged, so there is no concern about aggregation of the resin constituting the release coating, and there is no concern about the formation of protrusions, so it is not easy to produce pinholes in the resin sheet and it is preferred.
[0090] The surface free energy of the release layer provided on the substrate film of the present invention is 8 mJ / m 2 Above, for example, 10 mJ / m 2 Above, preferably 12mJ / m 2 For example, 18mJ / m 2 Above, it can be 20mJ / m 2 If it is 8mJ / m 2 The above is preferred because repellency or the like is less likely to occur when applying the solution of the resin sheet.
[0091] In the present invention, the surface free energy of the release layer satisfies the above conditions, thereby achieving both appropriate transferability of the release layer components to the resin sheet and adhesion to the base film in a well-balanced manner.
[0092] The surface free energy of the release layer provided on the substrate film of the present invention is preferably 40 mJ / m 2 More preferably 35 mJ / m 2 Below, more preferably 30mJ / m 2 Below. If 40mJ / m 2 The following is preferred because the releasability of the resin sheet after molding is good.
[0093] In the present invention, the surface free energy refers to at least the surface free energy of the surface of the release layer in contact with the resin sheet.
[0094] The water adhesion energy of the surface of the release layer in the present invention that contacts the resin sheet is, for example, 3.0 mJ / m 2 Above, can be 3.3mJ / m 2 Above, preferably 3.5mJ / m 2More preferably 4.0 mJ / m 2 More preferably, 5.5 mJ / m 2 If it is 3.0mJ / m 2 When the above is applied with the solution of the resin sheet, the bulge of the coating end is suppressed, which is preferred. When the bulge of the coating end during coating is suppressed, the protrusion (original Japanese: ear stand) when the laminated film is rolled into a roll is suppressed, and the roll shape becomes good, so the planarity of the laminated film becomes good, which is preferred. It should be noted that in this specification, water adhesion energy is sometimes simply referred to as adhesion energy.
[0095] In order to improve the water adhesion of the release layer surface, it can be achieved by adding additives to the release layer or adjusting the polymer composition. For example, in the case of a silicone resin, it can be improved by introducing a siloxane unit having a phenyl group in the side chain into the polydimethylsiloxane skeleton, or by adding a T unit (trifunctional) or a Q unit (quadrifunctional) silicone resin.
[0096] In order to improve the water adhesion energy of the release layer surface, as a method other than the above, it can also be achieved by changing the composition of the silicone resin. For example, for the silicone resin of the addition reaction system, polydimethylsiloxane with a vinyl group introduced into the terminal or side chain and hydrogen siloxane are heated under a platinum catalyst to be cured, and the molar amount of the Si-H group of the hydrogen siloxane is changed relative to the molar amount of the vinyl group (Si-Vy) at the terminal, thereby changing the water adhesion energy. For example, when Si-H is more than Si-Vy, the water adhesion energy tends to be higher, and the ratio of Si-H / Si-Vi is preferably 1.0 or more, more preferably 1.5 or more, and more preferably 2.0 or more.
[0097] For the release layer of the present invention, the arithmetic mean height (Sa) of not only the polyester substrate but also the release layer is preferably 20 nm or less. Furthermore, the arithmetic mean height (Sa) is particularly preferably 10 nm or less. If Sa is 20 nm or less, it is less likely to cause pinholes and local uneven thickness when the resin sheet is molded, which is preferred. The arithmetic mean height (Sa) of the release layer is preferably smaller, but it can also be 0.1 nm or more. For example, it is 0.2 nm or more.
[0098] In addition, the maximum protrusion height (P) of the release layer is, for example, 500 nm or less, preferably 200 nm or less, more preferably 150 nm or less, further preferably 100 nm or less, for example 85 nm or less, and particularly preferably 50 nm or less. If the maximum protrusion height (P) is 500 nm or less, pinholes and local thin filming will not occur when the resin sheet is formed, and the yield is good and preferred. The maximum protrusion height (P) of the release layer is 1 nm or more, for example 2 nm or more.
[0099] The force required for peeling the resin sheet of the present invention, that is, the peeling force of the release layer is, for example, 800 mN / 25 mm width or less. Within this range, the resin sheet of the present invention can be peeled off favorably.
[0100] The peeling force is preferably 300 mN / 25 mm width or less, for example 100 mN / 25 mm width or less. In particular, in the present invention, if the peeling force is 300 mN / 25 mm width or less, even a thin resin film can be prevented from being damaged during peeling.
[0101] In the present invention, the method for forming the release layer is not particularly limited, and the following method is used: a coating liquid in which a release resin is dissolved or dispersed is spread on one surface of the polyester film of the substrate by coating, the solvent is removed by drying, and then heat drying, thermal curing or ultraviolet curing is performed.
[0102] As a coating method for the release layer, any known coating method can be applied, for example, conventionally known methods such as gravure coating, roll coating such as reverse coating, rod coating such as wire bar, die coating, spray coating, and air knife coating can be used.
[0103] When a thermosetting material is used in the release layer, the drying temperature during solvent drying and heat curing is preferably 180°C or less, more preferably 160°C or less, further preferably 140°C or less, and most preferably 120°C or less. The heating time is preferably 30 seconds or less, more preferably 20 seconds or less, and most preferably 10 seconds or less. When the temperature is 180°C or less, the planarity of the film is maintained, and the concern of causing uneven thickness of the resin sheet is small, which is preferred. If it is 120°C or less, processing can be performed without destroying the planarity of the film, and the concern of causing uneven thickness of the resin sheet is further reduced, so it is particularly preferred.
[0104] The lower limit of the drying temperature is not particularly limited, but is preferably 60° C. or higher. When the drying temperature is 60° C. or higher, a release film can be obtained without residual solvent in the release layer, which is preferred.
[0105] When a UV curable material is used in the release layer, the drying temperature during solvent drying and heat curing is preferably 120°C or less, more preferably 100°C or less, and most preferably 90°C or less. The heating time is preferably 30 seconds or less, more preferably 20 seconds or less, and most preferably 10 seconds or less. When the temperature is below 120°C, the planarity of the film is maintained, and the concern about uneven thickness of the resin sheet is small, which is preferred. If it is below 90°C, processing can be performed without damaging the planarity of the film, and the concern about uneven thickness of the resin sheet is further reduced, so it is particularly preferred.
[0106] The lower limit of the drying temperature is not particularly limited, but is preferably 60° C. or higher. When the drying temperature is 60° C. or higher, a release film can be obtained without residual solvent in the release layer, which is preferred.
[0107] When a UV-curable material is used in the release layer, it is preferred to irradiate the active energy ray after the solvent is dried to carry out the curing reaction. As the active energy ray used, known techniques such as ultraviolet rays and electron beams can be used, and ultraviolet rays are preferably used. The cumulative light amount when ultraviolet rays are used can be expressed by the product of illuminance and irradiation time. For example, 10 to 500 mJ / cm is preferred. 2 By setting it to be above the aforementioned lower limit, the release layer can be sufficiently cured, which is preferred. By setting it to be below the aforementioned upper limit, thermal damage to the film caused by heat during irradiation can be suppressed, and the smoothness of the surface of the release layer can be maintained, which is preferred.
[0108] (resin sheet)
[0109] The laminated film of the present invention has a resin sheet disposed on a surface of the release layer opposite to the substrate.
[0110] For example, the resin sheet to be laminated on the release film of the present invention is obtained by curing a resin sheet-forming composition containing at least a resin component (A) and a crosslinking agent (B).
[0111] The resin sheet of the present invention has been studied extensively, and it has been found that by preparing the resin sheet-forming composition of the present invention under specific conditions described later, the resin component (A) and the crosslinking agent (B) can be cured in a phase-separated state, and appropriate irregularities can be formed on the surface of the resin sheet, thereby achieving the slipperiness of the resin sheet without containing particles in the resin sheet.
[0112] The total mass ratio of the resin component (A) and the crosslinking agent (B) is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more of the solid content of the entire resin sheet. If it contains 80% by mass or more, the physical properties of the resin sheet such as strength and heat resistance are improved, so it is preferred.
[0113] The mass ratio of the resin component (A) to the crosslinking agent (B) is preferably (A) / (B)=90 / 10 to 50 / 50. If the mixing ratio of the crosslinking agent (B) is 10% by mass or more, the unevenness after phase separation is easily increased, and the slippage is improved, so it is preferred. If the mixing ratio of the crosslinking agent (B) is 50% by mass or less, the film strength of the resin sheet will not decrease, and the operability as a sheet is excellent, so it is preferred, and it can also prevent the unreacted crosslinking agent from sticking to the back of the laminated film when winding. For example, the ratio of the crosslinking agent (B) contained in the resin sheet to the entire resin sheet is preferably 10% by mass or more and 50% by mass or less. In one embodiment, when the total solid content of the resin sheet is set to 100% by mass, the ratio of the crosslinking agent (B) contained in the resin sheet to the entire resin sheet is 10% by mass or more, for example, 10% by mass or more and less than 50% by mass, for example, 15% by mass or more and 45% by mass or less. By including the crosslinking agent (B) under such conditions, the above-mentioned effects can be more preferably exhibited.
[0114] As the resin component (A), there is no particular limitation, and known resins can be used. For example, epoxy resins, phenoxy resins, polyester resins, polyurethane resins, fluorine resins, acrylic resins, olefin resins, imide resins, sulfone resins, etc. can be used, and one kind can be used, or two or more kinds can be mixed and used. The weight average molecular weight (Mw) of the resin component (A) used in the present invention is more than 10,000, preferably more than 10,000 and less than 200,000, more preferably more than 30,000 and less than 100,000. If the weight average molecular weight (Mw) is more than 10,000, the strength of the resin sheet is strong and the operability is good, so it is preferred. If it is less than 200,000, the viscosity of the solution becomes low when the solution is film-formed, and the productivity becomes good, so it is preferred. The method for measuring the weight average molecular weight (Mw) is not particularly limited, and it can be measured by GPC, etc.
[0115] There is no particular limitation on the crosslinking agent (B), and known crosslinking agents can be used. For example, crosslinking agents such as isocyanate, melamine, carbodiimide, and oxazoline can be used, and one type can be used, or two or more types can be mixed and used. Preferably, it is formed by reacting with the functional groups contained in the resin component (A). The crosslinking agent (B) contained in the resin sheet forming composition is preferably liquid at 30°C. In the present invention, the liquid only needs to have fluidity, for example, the viscosity only needs to be 10000 mPa·s or less. By being liquid at 30°C, the phase separation from the resin component (A) during the drying of the solution film of the resin sheet can be effectively promoted, and the surface unevenness of the resin sheet becomes easy to form, so it is preferred.
[0116] In the resin sheet, additives other than the resin component (A) and the crosslinking agent (B) may be included as long as the above range is met. Among them, in the present invention, the resin sheet is substantially free of particles. The resin sheet of the present invention is substantially free of particles, so that, for example, if it is for optical purposes, it is easy to obtain the effect of increasing the transparency of the resin sheet after molding, and improving the electrical characteristics of electronic components such as dielectric sheets used in film capacitors, so it is preferred. For example, if it is for optical purposes, the haze of the resin sheet can be less than 2%. In addition, the haze can be less than 1%. In one embodiment, the haze of the resin sheet is more than 0.1%. In addition, for example, if it is an electronic component such as a film capacitor, the dielectric breakdown voltage of the resin sheet can be more than 200V / μm. In addition, the dielectric breakdown voltage can be more than 300V / μm. In one embodiment, the dielectric breakdown voltage is less than 500V / μm.
[0117] The details of the technical feature "the resin sheet does not substantially contain particles" can be explained by applying the above contents about the base material to the resin sheet.
[0118] In the resin sheet, as an additive material mixed with the resin component (A) and the crosslinking agent (B), it is preferred that the additive material has good compatibility with the resin component (A) and can react with the crosslinking agent (B). For example, polyurethane, polyester, polyketone, polyol, polyarylate, phenoxy resin, epoxy resin, etc. are preferred. For example, when isocyanate is used as the crosslinking agent, polyol-based resins are also preferred.
[0119] Even if the resin sheet of the present invention does not substantially contain particles, there are tiny concave-convex surfaces on the surface caused by the phase separation of the resin component (A) and the crosslinking agent (B), so it can have good sliding properties. The static friction coefficient (μs) of the resin sheet peeled off from the substrate film is preferably 1.5 or less, more preferably 1.0 or less, and further preferably 0.8 or less. The static friction coefficient is 1.5 or less, so when it is used as a resin sheet in optical applications and electronic component applications, the winding property, the running property, etc. are good, and the operation becomes easy, so it is preferred. The static friction coefficient of the resin sheet can be 0.1 or more.
[0120] In one way, Figure 2 In the embodiment, the static friction coefficient measured by overlapping the surface (1) of the resin sheet 12 on the opposite side to the release layer 11 and the surface (2) of the resin sheet on the release layer side indicated by reference numeral 14 is 1.5 or less. The static friction coefficient measured under the above conditions is more preferably 1.0 or less, and further preferably 0.8 or less. In addition, the static friction coefficient may be 0.1 or more.
[0121] As described above, when the static friction coefficient measured by overlapping both surfaces of the resin sheet is within the above range, the resin sheet of the present invention can have both high smoothness and excellent windability and running properties.
[0122] The surface (1) of the resin sheet of the laminated film of the present invention, that is, the surface (1) of the resin sheet on the opposite side to the release layer, has an arithmetic mean roughness (Sa) of 2 nm or more and 30 nm or less, more preferably 2 nm or more and 20 nm or less, and further preferably 2.5 nm or more and 15 nm or less. If it is 2 nm or more, the sliding property of the resin sheet becomes good and it is preferred. If it is 30 nm or less, when the resin sheet is peeled off from the laminated film and the resin sheet is simply wound into a roll, the concern about the generation of pinholes and other bad spots is also reduced and it is preferred.
[0123] The surface opposite to the surface in contact with the release layer may be simply referred to as the surface (1) of the resin sheet.
[0124] The maximum cross-sectional height (St) of the surface (1) of the resin sheet of the laminated film of the present invention, that is, the surface (1) of the resin sheet on the opposite side to the release layer, is 80 nm or more and 1000 nm or less, more preferably 100 nm or more and 600 nm or less, and further preferably 150 nm or more and 500 nm or less. If it is 80 nm or more, the sliding property of the resin sheet becomes good and it is preferred. If it is 1000 nm or less, when the resin sheet is peeled off from the laminated film and the resin sheet is simply wound into a roll, the concern about the generation of bad spots such as pinholes is also reduced and it is preferred.
[0125] It should be noted that the maximum cross-sectional height (St) is a value obtained by adding the absolute value of the maximum protrusion height (P) and the maximum valley depth (V).
[0126] The maximum protrusion height (P) of the surface (1) of the resin sheet of the laminated film of the present invention, that is, the surface (1) of the resin sheet on the opposite side to the release layer, is preferably 500 nm or less, more preferably 260 nm or less, further preferably 200 nm or less, and may be 185 nm or less, for example 150 nm or less, particularly preferably 135 nm or less. For example, it may be 100 nm or less.
[0127] If the maximum protrusion height (P) of the surface (1) of the resin sheet is 500 nm or less, then when the resin sheet is peeled off from the laminated film and simply rolled up into a roll, no pinhole or other defective spots are generated, which is preferred. The maximum protrusion height P is preferably as small as possible, but may be 1 nm or more, 3 nm or more, for example, 35 nm or more.
[0128] By setting the arithmetic mean roughness (Sa) and the maximum cross-sectional height (St) of the surface (1) of the resin sheet of the laminated film of the present invention to the aforementioned ranges, good sliding properties can be obtained even on a surface with high smoothness. It is particularly preferred to control the maximum cross-sectional height (St) to the aforementioned range.
[0129] In one embodiment, the maximum valley depth (V) of the surface (1) of the resin sheet of the laminated film is preferably 45 nm to 350 nm, for example, 45 nm to 300 nm, preferably 45 nm to 250 nm. When the maximum valley depth (V) is within such a range, even if the maximum protrusion height (P) is within a range of 250 nm or less, it becomes easy to control the maximum cross-sectional height (St) within the aforementioned range, and the sliding property of the resin sheet can be improved, which is preferred.
[0130] The arithmetic mean roughness (Sa) of the surface (2) of the resin sheet of the laminated film of the present invention, i.e., the surface (2) on the release layer side of the resin sheet, is preferably 10 nm or less, more preferably 8 nm or less, and further preferably 5 nm or less. If it is 10 nm or less, the concern of forming pinholes or other defects when the resin sheet is peeled off from the laminated film and simply rolled up into a roll is reduced, which is preferred.
[0131] The surface (2) of the resin sheet is preferably a surface in contact with the release layer.
[0132] The film thickness (t1) of the resin sheet of the present invention is 1 μm or more and 20 μm or less. It is more preferably 1 μm or more and 10 μm or less, and further preferably 2 μm or more and 8 μm or less. If the film thickness (t1) of the resin sheet is 1 μm or more, it is not easy to break even after being peeled off from the substrate film, and it can be easily handled, so it is preferred. If the film thickness (t1) of the resin sheet is 20 μm or less, the wet coating film thickness does not become excessively thick during solution film formation, and molding is easy, so it is preferred.
[0133] The film thickness (t1) of the resin sheet is not particularly limited and can be measured by a known method, for example, a contact film thickness meter, an optical interference film thickness meter, or by cross-sectional observation using a scanning electron microscope or a transmission electron microscope.
[0134] As a method for laminating the resin sheet of the present invention on a substrate film, it is preferred that a coating liquid (i.e., a resin sheet forming composition) containing at least the above-mentioned resin component (A) and the crosslinking agent (B) and dissolved or dispersed in an organic solvent, water, etc. is applied on the release layer by a solution film-forming method and molded. The coating can be performed by a known method similar to the coating method of the release layer. For example, a conventionally known method such as a roll coating method such as a gravure coating method, a reverse coating method, a rod coating method such as a wire rod, a die coating method, a spray coating method, an air knife coating method, etc. can be used.
[0135] After the coating liquid is applied to the release layer, a heating step is preferably provided in order to dry and solidify the solvent. The heating method is not particularly limited, and the coated laminated film can be heated by hot air, infrared rays, etc. The laminated film of the present invention is preferably coated and dried by roll-to-roll, and the drying furnace is particularly preferably dried by hot air using a floating method, a roller support method, etc.
[0136] The temperature during drying is as follows: the maximum temperature of the drying furnace is preferably above 60°C and below 160°C, more preferably above 70°C and below 140°C, and further preferably above 70°C and below 130°C. If it is above 60°C, there is less residual solvent in the resin sheet after drying, and there is no concern about the performance of the resin sheet (for example, electrical properties if it is used as a dielectric layer) being reduced, so it is preferred. If it is below 160°C, there is no concern about wrinkles in the laminated film due to heat, so it is preferred. In addition, if it is higher than 160°C, there is a concern that the phase separation of the resin component and the crosslinking agent in the resin sheet is excessive and the crosslinking density of the resin sheet is reduced, so it is preferably set to below 160°C.
[0137] The time from coating the coating liquid on the substrate film to entering the drying furnace is preferably within 5 seconds, more preferably within 3 seconds, and further preferably within 2 seconds. If it is within 5 seconds, the phase separation between the resin component and the crosslinking agent in the coating liquid does not proceed excessively, and there is no concern about a decrease in the crosslinking density of the resin sheet.
[0138] After the coating liquid is applied to the substrate film, the time for heating at the maximum temperature in the drying furnace is preferably 1 second or more, preferably 2 seconds or more. If it is 1 second or more, the reaction of the crosslinking agent proceeds, so it is preferred. The upper limit of the heating time is preferably within 60 seconds, more preferably within 40 seconds, and further preferably within 20 seconds. If it is within 60 seconds, it is possible to suppress the segregation of the crosslinking agent on the surface of the resin sheet, and the performance of the resin sheet is not reduced, so it is preferred.
[0139] By setting the resin sheet of the present invention to the above-mentioned drying conditions, the phase separation of the resin component (A) and the crosslinking agent (B) can be appropriately performed, and the arithmetic mean roughness (Sa) and the maximum cross-sectional height (St) of the resin sheet surface (1) can be controlled within the above-mentioned ranges, and the good sliding property of the resin sheet can be exhibited without adding particles to the resin sheet.
[0140] (Laminated Film)
[0141] The laminated film of the present invention is used by peeling off the resin sheet from the release layer laminated on the substrate film in the following process and thereafter. Therefore, if the peeling force from the release layer laminated on the substrate film is 800mN / 25mm width or less, the resin sheet can be peeled off without breaking, etc., so it is preferred. More preferably, it is 500mN / 25mm width or less, further preferably 300mN / 25mm width or less, and further preferably 200mN / 25mm width or less. The peeling force varies depending on the laminated resin sheet, and therefore, it can be adjusted according to the type of the release layer laminated on the substrate film.
[0142] (Laminated film roll)
[0143] The laminated film having a resin sheet laminated on a substrate film is preferably wound into a roll after the resin sheet is laminated. When wound into a roll, it is preferably wound under appropriate winding conditions to avoid crushing the unevenness formed on the surface of the resin sheet by phase separation. As long as the surface unevenness satisfies the static friction coefficient of the resin sheet after winding, it can be wound in a known manner, and the winding conditions are not particularly limited. In more detail, the winding is carried out under the condition that the static friction coefficient measured by overlapping the surface (1) of the resin sheet on the opposite side of the release layer with the surface (2) on the release layer side of the resin sheet is less than 1.5. It should be noted that although it is simply referred to as surface unevenness, it specifically refers to the surface shape recorded in this specification such as the arithmetic mean height (Sa) and the maximum cross-sectional height (St).
[0144] In one embodiment, the laminate film is wound under the following conditions. The initial winding tension at the beginning of winding when the laminate film of the present invention is wound is preferably greater than 20 N / m and less than 400 N / m, more preferably greater than 25 N / m and less than 300 N / m. It is also preferably greater than 30 N / m and less than 250 N / m. If it is greater than 20 N / m, the winding shape becomes good and no winding misalignment occurs, so it is preferred. In addition, if it is less than 400 N / m, the stress in the radial direction of the film roll after winding does not become excessively high, and the unevenness on the surface of the laminate film is not easily crushed, which is preferred. (The unit N / m represents the tension N when converted to the width of the substrate film 1 m). The initial winding tension can be derived by measuring the winding tension of the roll.
[0145] The winding tension of the roll surface layer at the end of winding when the laminated film of the present invention is wound is preferably 20N / m or more and 360N / m or less, more preferably 25N / m or more and 300N / m or less. It is also preferably 30N / m or more and 250N / m or less. If it is 20N / m or more, the winding shape becomes good and no winding dislocation occurs, so it is preferred. In addition, if it is 360N / m or less, the stress in the radial direction of the film roll after winding does not become excessively high, and the unevenness on the surface of the laminated film is not easily crushed, so it is preferred.
[0146] It is preferred to add a taper to the winding tension so that the winding tension of the surface layer of the roll is the same as or lower than the initial winding tension. The winding tension of the surface layer of the roll is T E , the winding tension of the coil (initial winding tension) is set to T S It is preferred that the following formula is satisfied.
[0147] 0.2≤T E / T S ≤1
[0148] By winding under the conditions having the above relationship, it is possible to well derive that the static friction coefficient measured by overlapping the surface (1) of the resin sheet of the present invention on the opposite side of the release layer with the surface (2) on the release layer side of the resin sheet is 1.5 or less. In addition, the surface shape of the resin sheet can be maintained. As a result, the resin sheet can have high smoothness and sliding properties in a well-balanced manner, and the effects described in this specification can be more significantly exerted.
[0149] When the laminated film of the present invention is wound up, it is preferred to use a touch roll for winding up. The material, diameter, and conditions of the touch roll are not particularly limited.
[0150] The roll hardness of the surface of the laminated film roll of the present invention is preferably 900 or less, more preferably 850 or less, and still more preferably 750 or less. If it is 900 or less, the irregularities on the surface of the resin sheet are not easily crushed, which is preferred.
[0151] The roll hardness of the surface of the laminated film roll of the present invention is preferably 400 or more, more preferably 450 or more, and still more preferably 480 or more. If it is 400 or more, the laminated film will not be misaligned in winding, which is preferred.
[0152] The coil hardness can be adjusted to a suitable range by satisfying the above-mentioned coiling conditions.
[0153] It is particularly suitable to set the taper so that the initial winding tension and the winding tension of the roll surface layer are within the above range. In addition, the surface roll hardness of the laminated film roll can be measured by measuring the hardness of the layer present on the outermost side of the laminated film roll, that is, the resin sheet located on the surface of the laminated film roll.
[0154] The roll length of the laminated film roll of the present invention is not particularly limited, but is preferably 3000 m or longer, more preferably 6000 m or longer, further preferably 12000 m or longer, and further preferably 18000 m or longer.
[0155] The width of the laminated film roll of the present invention is not particularly limited, but the lower limit is preferably 200 mm or more, more preferably 300 mm or more, and further preferably 450 mm or more, and the upper limit is preferably 2000 mm or less. Specific embodiments
[0157] Next, the present invention will be described in detail using examples and comparative examples, but the present invention is not limited to the following examples. In addition, the evaluation method used in the present invention is as follows.
[0158] (Arithmetic mean height (Sa), maximum protrusion height (P), maximum valley depth (V), maximum cross-sectional height (St))
[0159] The value is measured using a non-contact surface shape measurement system (Ryoka Systems Inc. VertScan R550H-M100) under the following conditions. The arithmetic mean height (Sa) is the average of 5 measurements, the maximum protrusion height (P) and the maximum valley depth (V) are measured 7 times, and the 5 maximum values excluding the maximum and minimum values are used. The maximum cross-sectional height (St) is the value obtained by adding the absolute values of the maximum protrusion height (P) and the maximum valley depth (V).
[0160] (Measurement conditions)
[0161] ·Measurement mode: WAVE mode
[0162] Objective lens: 10 times
[0163] 0.5×Tube lens
[0164] ·Measurement area 936μm×702μm
[0165] (Analysis conditions)
[0166] ·Surface correction: 4 times correction
[0167] Interpolation processing: Full interpolation
[0168] Filter processing: Gaussian cutoff value 50μm
[0169] (Surface free energy)
[0170] Under the conditions of 25°C and 50% RH, a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.: Fully Automatic Contact Angle Meter DM-701) was used to make drops of water (drop volume 1.8 μL) and diiodomethane (liquid volume 0.9 μL) on the release surface of the release film, and the contact angle was measured. The contact angle used is the contact angle 10 seconds after each liquid was dropped on the release film. The contact angle data of water and diiodomethane obtained by the above method were calculated according to the "Owens and Wendt" theory, and the component γh was calculated based on the dispersed component γd, hydrogen bonds and dipole-dipole interactions of the surface free energy of the release film, and the total of each component was taken as the surface free energy γs. In this calculation, the analytical software in this contact angle meter software (FAMAS) was used.
[0171] (Water Adhesion Energy)
[0172] Under the conditions of 25°C and 50% RH, water (10 μL droplet) was dripped onto the release surface of the release film using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.: Fully Automatic Contact Angle Meter DM-701). The stage was tilted continuously 2 seconds after the dripping, and the contact angle was measured for each 1° tilt. In addition, the tilt angle when the droplet position moves 5 dots from 0° was determined as the sliding angle, and the adhesion energy was calculated from this. In this calculation, the analytical software in this contact angle meter software (FAMAS) was used.
[0173] (Wettability Evaluation)
[0174] Use a winding rod to apply the following resin coating solution on the release surface of the release film in such a way that the thickness of the resin sheet after drying becomes 3μm, and dry it in a hot air oven at 120°C for 30 seconds. Measure the coating width (W1) just after the resin solution is applied and the width (W2) of the resin film after drying. As shown in the following formula, half of the difference between the coating width (W1) and the width (W2) of the resin film is taken as the end depression width. The wettability is evaluated based on the measured end depression width according to the following criteria.
[0175] Width of end depression [mm] = (W1-W2) / 2
[0176] (resin solution)
[0177] Methyl ethyl ketone 41.3 parts by mass
[0178] 22.5 parts by mass of tetrahydrofuran 30.6 parts by mass of PKHB solution (solid content 40% by mass)
[0179] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0180] * The solution is 5.3 parts by mass of Millionate MTL (manufactured by Tosoh Corporation, isocyanate crosslinking agent, viscosity 50 mPa·s, solid content 99% by mass) prepared by dissolving a phenoxy resin in tetrahydrofuran
[0181] BYK-370 0.4 parts by mass
[0182] (Wettability Evaluation Criteria)
[0183] 0:0≤End recess width[mm]≤3
[0184] △: 3<End recess width [mm] ≤ 6
[0185] ×: 6<End recess width [mm]
[0186] (film thickness)
[0187] The cut laminated film was embedded in a resin and sliced into ultrathin slices using an ultramicrotome, and then observed using a JEM2100 transmission electron microscope manufactured by JEOL Ltd. at a direct magnification of 20,000 times, and the film thickness of each layer of the laminated film was measured from the observed TEM image.
[0188] (Peel force)
[0189] The laminated film was cut into strips of 25 mm in width and 150 mm in length, one end of the substrate film and the release layer was fixed, one end of the resin sheet was supported, and the resin sheet side was stretched at a speed of 300 mm / min to measure the T-peel strength. A tensile tester ("AUTOGRAPH AG-X" manufactured by Shimadzu Corporation) was used in the measurement. The measured value was the average value of 5 measurements.
[0190] The peeling property was evaluated based on the measured peeling force according to the following criteria.
[0191] ○: Can be peeled with a low peel force of 100mN / 25mm width or less, and can be peeled without cracking in laminated films
[0192] ○△: Peeling can be performed with a peeling force of 300 mN / 25 mm width or less and greater than 100 mN / 25 mm width.
[0193] △: The film can be peeled off with a peeling force of more than 300mN / 25mm width and less than 800mN / 25mm width. In the extremely thin part of the film, a part of the film may be broken.
[0194] ×: Peeling was not possible.
[0195] (Static friction coefficient and sliding property evaluation)
[0196] The static friction coefficient of the resin sheet was measured as follows to evaluate the sliding property.
[0197] The resin sheet was peeled off from the laminated film and fixed to the bottom of a metal rectangular parallelepiped weighing 1.4 kg so that the surface (2) of the resin sheet was facing upward. Next, the resin sheet was fixed to a flat metal plate with an adhesive tape so that the surface (1) of the resin sheet was facing upward. The metallic rectangular parallelepiped was placed so that the surface (1) was in contact with the surface (2), and the static friction coefficient was measured at 23°C and 65%RH at a tensile speed of 200 mm / min.
[0198] The sliding properties were judged based on the following criteria.
[0199] ○:0.1<μs≤0.8
[0200] △: 0.8<μs≤1.5
[0201] ×: Exceeds 1.5 or the friction coefficient is too high to be measured
[0202] (Electrical Characteristics)
[0203] Thin aluminum vapor-deposited layers were provided on both sides of a resin sheet separated from a release layer laminated on a substrate film, and dielectric breakdown voltage (V / μm) was measured at room temperature. Evaluation was performed using the average value of 10 points measured according to the following criteria.
[0204] ○: Dielectric breakdown voltage (BDV value) is 300V / μm or more
[0205] △: Dielectric breakdown voltage is 200V / μm or more
[0206] ×: Dielectric breakdown voltage is less than 200V / μm
[0207] (Roll hardness of laminated film roll)
[0208] The surface of the obtained laminated film roll was measured using a film roll hardness tester (FTS-Roll Tester 1, manufactured by FTS., LTD.). The measurement was performed as follows: 5 points were measured evenly along the width direction except for 3 cm at both ends of the film roll. n=3 measurements were performed at each measurement point, and the average value of a total of 15 points was used.
[0209] (Preparation of polyethylene terephthalate pellets (PET (I)))
[0210] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a three-stage complete mixing tank having a stirring device, a partial condenser, a raw material inlet, and a product outlet was used. TPA (terephthalic acid) was set to 2 tons / hour, EG (ethylene glycol) was set to 2 mol per 1 mol of TPA, and antimony trioxide was set to 160 ppm with respect to the generated PET and Sb atoms. These slurries were continuously supplied to the first esterification reaction kettle of the esterification reaction apparatus, and the reaction was carried out at 255° C. at an average residence time of 4 hours under normal pressure. Next, the reaction product in the first esterification reactor was continuously taken out of the system and supplied to the second esterification reactor. To the second esterification reactor, EG distilled from the first esterification reactor was supplied in an amount of 8% by mass relative to the produced PET. Furthermore, an EG solution containing 65 ppm of magnesium acetate tetrahydrate and 40 ppm of TMPA (trimethyl phosphate) relative to the produced PET were added to react at 260° C. with an average residence time of 1 hour at normal pressure. Next, the reaction product in the second esterification reactor was continuously taken out of the system and supplied to the third esterification reactor. The EG solution was dispersed at 39 MPa (400 kg / cm 2) were dispersed for an average of 5 times under a pressure of 100°C and 0.2% by mass of porous colloidal silica with an average particle size of 0.9 μm and 0.4% by mass of synthetic calcium carbonate with an average particle size of 0.6 μm of ammonium salt of polyacrylic acid attached to 1% by mass relative to unit calcium carbonate were added as 10% EG slurry, and reacted at 260°C at an average residence time of 0.5 hours under normal pressure. The esterification reaction product generated in the third esterification reaction kettle was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, filtered through a filter made of sintered stainless steel fibers with a cut diameter of 20 μm at 95%, and then ultrafiltered, extruded into water, and cut into small pieces after cooling to obtain PET small pieces with a characteristic viscosity of 0.60 dl / g (hereinafter referred to as PET (I)). The lubricant content in the PET small pieces was 0.6% by mass.
[0211] (Preparation of polyethylene terephthalate pellets (PET(II)))
[0212] On the other hand, in the production of the above-mentioned PET chips, PET chips having an intrinsic viscosity of 0.62 dl / g (hereinafter referred to as PET (II)) containing no particles of calcium carbonate, silicon dioxide, etc. were obtained.
[0213] (Preparation of polyethylene terephthalate pellets (PET(III)))
[0214] PET chips (hereinafter referred to as PET (III)) were obtained in the same manner as PET (I), except that the type and content of PET (I) particles were changed to 0.75% by mass of synthetic calcium carbonate having an average particle size of 0.9 μm and 1% by mass of ammonium salt of polyacrylic acid attached to each unit of calcium carbonate. The lubricant content in the PET chips was 0.75% by mass.
[0215] (Manufacturing of Base Film X1)
[0216] After drying, these PET chips were melted at 285°C, melted at 290°C by another melt extruder, and subjected to two-stage filtration using a filter formed by sintering 95% stainless steel fibers with a cut diameter of 15 μm and a filter formed by sintering 95% stainless steel particles with a cut diameter of 15 μm. The PET chips were merged in a feed block, laminated in such a manner that PET (I) became the surface layer B and PET (II) became the surface layer A, extruded (cast) into a sheet at a rate of 45 m / min, and electrostatically bonded / cooled on a casting drum at 30°C by an electrostatic bonding method to obtain an unstretched polyethylene terephthalate sheet having an intrinsic viscosity of 0.59 dl / g. The layer ratio was adjusted so that PET (I) / PET (II) = 60% / 40% was calculated based on the discharge amount of each extruder. Next, the unstretched sheet was heated in an infrared heater and stretched 3.5 times in the longitudinal direction at a roll temperature of 80°C according to the speed difference between the rolls. After that, it was introduced into a tenter and stretched 4.2 times in the transverse direction at 140°C. Then, it was heat treated at 210°C in a heat setting zone. After that, it was relaxed 2.3% in the transverse direction at 170°C to obtain a substrate film X1 of a biaxially stretched polyethylene terephthalate film having a thickness of 25 μm. The Sa of the surface layer A of the obtained substrate film X1 was 2 nm, and the Sa of the surface layer B was 29 nm.
[0217] (Manufacturing of Base Film X2 Having Release Layer)
[0218] On the surface layer A of the substrate film X1 obtained above, the following release coating liquid Y1 was applied by reverse gravure coating to a wet film thickness of 5 μm, and dried / cured in a hot air drying oven at 120° C. for 30 seconds to obtain a substrate film X2 with a release layer. The Sa of the release layer surface was 2 nm.
[0219] (Mold release coating liquid Y1)
[0220] Toluene 48 parts by mass
[0221] 48 parts by mass of methyl ethyl ketone
[0222] Silicone resin composition (1)
[0223] (Thermosetting silicone coating, Si-H / Si-Vy=3.0, solid content 30% by mass)
[0224] 3 parts by mass
[0225] SRX212P Catalyst (Pt-based curing catalyst manufactured by Dow Toray Co., Ltd.)
[0226] 0.1 parts by mass
[0227] (Manufacturing of Base Film X3 Having Release Layer)
[0228] Without changing the layer structure and stretching conditions of the substrate film X1, the casting speed was changed to adjust the thickness, and a biaxially stretched polyethylene terephthalate film with a thickness of 12 μm was prepared, and a release layer similar to X2 was provided to obtain a substrate film X3. The Sa of the surface layer A of the obtained film X3 was 3 nm, and the Sa of the surface layer B was 29 nm.
[0229] (Method for producing base film X4 having release layer)
[0230] As the base film X4, A4100 (Cosmoshine (registered trademark), manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm was used, in which a release layer similar to X2 was provided on the surface layer A. A4100 was configured as follows: the film substantially contained no particles, and a coating layer containing particles was provided by in-line coating only on the surface layer B side. The Sa of the surface layer A of the base film X4 was 1 nm, and the Sa of the surface layer B was 2 nm.
[0231] (Method for producing base film X5 having release layer)
[0232] As the base film X5, a film having a thickness of 25 μm, E5101 (TOYOBO ESTER (registered trademark) film, manufactured by Toyobo Co., Ltd.) was used in which a release layer similar to X2 was provided on the surface layer A. E5101 has a structure in which particles are contained in the surface layers A and B of the film. The Sa of the surface layer A of the base film X5 was 25 nm, and the Sa of the surface layer B was 25 nm.
[0233] (Method for producing base film X6 having release layer)
[0234] The following release coating liquid Y2 was applied to the surface layer A of the substrate film X1 by reverse gravure coating to a wet film thickness of 5 μm, and dried / cured in a hot air drying oven at 120° C. for 30 seconds to obtain a substrate film X6 with a release layer. The surface Sa of the release layer was 2 nm.
[0235] (Mold release coating liquid Y2)
[0236] Toluene 48 parts by mass
[0237] 48 parts by mass of methyl ethyl ketone
[0238] Silicone resin composition (2)
[0239] (Thermosetting silicone coating, Si-H / Si-Vy=1.0, solid content 30% by mass)
[0240] 3 parts by mass
[0241] SRX212P Catalyst (Pt-based curing catalyst manufactured by Dow Toray Co., Ltd.)
[0242] 0.1 parts by mass
[0243] (Method for producing base film X7 having release layer)
[0244] The following release coating liquid Y3 was applied to the surface layer A of the substrate film X1 by reverse gravure coating to a wet film thickness of 5 μm, and dried / cured in a hot air drying oven at 120° C. for 30 seconds to obtain a substrate film X7 with a release layer. The surface Sa of the release layer was 2 nm.
[0245] (Mold release coating liquid Y3)
[0246] Toluene 48 parts by mass
[0247] 48 parts by mass of methyl ethyl ketone
[0248] Silicone resin composition (3)
[0249] (Thermosetting silicone coating, Si-H / Si-Vy=2.2, solid content 30% by mass)
[0250] 3 parts by mass
[0251] SRX212P Catalyst (Pt-based curing catalyst manufactured by Dow Toray Co., Ltd.)
[0252] 0.1 parts by mass
[0253] (Example 1)
[0254] The resin solution Z1 was applied to the surface layer A, i.e., the release layer, of the substrate film X2 (width 1300 mm, roll length 12500 m) by reverse gravure coating so that the film thickness of the dried resin sheet was 3 μm, and dried in a hot air drying furnace at 120° C. for 10 seconds, and then rolled up in a roll shape with an initial winding tension of 100 N / m and a surface winding tension of 60 N / m to produce a laminated film (width 1200 mm, roll length 12000 m) formed into a resin sheet. (At this time, it takes 2 seconds from coating until entering the drying furnace). The details are shown in Table 1A and Table 2A.
[0255] (Resin solution Z1)
[0256] Methyl ethyl ketone 41.3 parts by mass
[0257] 22.5 parts by mass of tetrahydrofuran
[0258] PKHB solution (solid content 40% by mass) 30.6 parts by mass
[0259] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0260] * The solution is prepared by dissolving a phenoxy resin in tetrahydrofuran: 5.3 parts by mass of Millionate MR-200 (manufactured by Tosoh Corporation, isocyanate crosslinking agent, viscosity 200 mPa·s, solid content 99% by mass)
[0261] BYK-370 0.4 parts by mass
[0262] (BYK Japan Co., Ltd., silicone-based surfactant)
[0263] (Examples 2-3)
[0264] Except having changed the base film and the release layer into the thing described in Table 1, it carried out similarly to Example 1, and produced the laminated film roll.
[0265] (Example 4)
[0266] A laminated film roll was produced in the same manner as in Example 1 except that the resin component (A) was changed to a resin solution Z6 having a different weight average molecular weight (Mw).
[0267] (Resin solution Z7)
[0268] Methyl ethyl ketone 41.3 parts by mass
[0269] 22.5 parts by mass of tetrahydrofuran
[0270] PKHJ solution (solid content 40% by mass) 30.6 parts by mass (phenoxy resin manufactured by Gabriel Phenoxies, Mw 57000)
[0271] * The solution is prepared by dissolving a phenoxy resin in tetrahydrofuran: 5.3 parts by mass of Millionate MR-200 (manufactured by Tosoh Corporation, isocyanate crosslinking agent, viscosity 200 mPa·s, solid content 99% by mass)
[0272] BYK-370 0.4 parts by mass
[0273] (BYK Japan Co., Ltd., silicone-based surfactant)
[0274] (Example 5)
[0275] A laminated film roll was produced in the same manner as in Example 1 except that the type of the crosslinking agent was changed to the resin solution Z2.
[0276] (Resin solution Z2)
[0277] Methyl ethyl ketone 41.3 parts by mass
[0278] 22.5 parts by mass of tetrahydrofuran 30.6 parts by mass of PKHB solution (solid content 40% by mass) (phenoxy resin manufactured by Gabriel Phenoxies, Mw 32000)
[0279] * The solution is prepared by dissolving a phenoxy resin in tetrahydrofuran: 5.3 parts by mass of Millionate MR-400 (manufactured by Tosoh Corporation, isocyanate crosslinking agent, viscosity 600 mPa·s, solid content 99% by mass)
[0280] BYK-370 0.4 parts by mass
[0281] (BYK Japan Co., Ltd., silicone-based surfactant)
[0282] (Example 6)
[0283] A laminated film roll was produced in the same manner as in Example 1 except that the type of the crosslinking agent was changed to the resin solution Z3.
[0284] (Resin solution Z3)
[0285] Methyl ethyl ketone 41.3 parts by mass
[0286] 22.5 parts by mass of tetrahydrofuran
[0287] PKHB solution (solid content 40% by mass) 30.6 parts by mass
[0288] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0289] * The solution is 5.3 parts by mass of Millionate MTL prepared by dissolving phenoxy resin in tetrahydrofuran
[0290] (Tosoh Corporation, isocyanate crosslinking agent, viscosity 50 mPa·s, solid content 99 mass %)
[0291] BYK-370 0.4 parts by mass
[0292] (BYK Japan Co., Ltd., silicone-based surfactant)
[0293] (Example 7)
[0294] A laminated film roll was produced in the same manner as in Example 1 except that the resin solution was changed to the resin solution Z4 in order to change the ratio of the resin to the crosslinking agent.
[0295] (Resin solution Z4)
[0296] Methyl ethyl ketone 41.3 parts by mass
[0297] 19.9 parts by mass of tetrahydrofuran
[0298] PKHB solution (solid content 40% by mass) 35.0 parts by mass
[0299] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0300] * The solution is 3.5 parts by mass of Millionate MR-200 prepared by dissolving phenoxy resin in tetrahydrofuran
[0301] (Tosoh Corporation, isocyanate crosslinking agent, viscosity 200 mPa·s, solid content 99 mass %)
[0302] BYK-370 0.4 parts by mass
[0303] (BYK Japan Co., Ltd., silicone-based surfactant)
[0304] (Example 8)
[0305] A laminated film roll was produced in the same manner as in Example 1 except that the resin solution was changed to the resin solution Z5 in order to change the ratio of the resin to the crosslinking agent.
[0306] (Resin solution Z5)
[0307] Methyl ethyl ketone 41.3 parts by mass
[0308] 17.3 parts by mass of tetrahydrofuran
[0309] PKHB solution (solid content 40% by mass) 39.4 parts by mass
[0310] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0311] * The solution is 1.8 parts by mass of Millionate MR-200 prepared by dissolving phenoxy resin in tetrahydrofuran
[0312] (Tosoh Corporation, isocyanate crosslinking agent, viscosity 200 mPa·s, solid content 99 mass %)
[0313] BYK-370 0.4 parts by mass
[0314] (BYK Japan Co., Ltd., silicone-based surfactant)
[0315] (Examples 9 to 11)
[0316] A laminated film roll was prepared in the same manner as in Example 1 except that the base film with a release layer described in Table 1 was used.
[0317] (Examples 12-13)
[0318] Except having changed the drying temperature of a resin sheet into the temperature described in Table 1, it carried out similarly to Example 1, and produced the laminated film roll.
[0319] (Examples 14-15)
[0320] Except having changed the winding tension into the condition described in Table 1, it carried out similarly to Example 1, and produced the laminated film roll.
[0321] (Comparative Example 1)
[0322] A laminated film roll was prepared in the same manner as in Example 1 except that the base film was changed to X1 having no release layer.
[0323] (Comparative Example 2)
[0324] A laminated film roll was produced in the same manner as in Example 1 except that the resin solution was changed to a resin solution Z6 not containing a crosslinking agent.
[0325] (Resin solution Z6)
[0326] Methyl ethyl ketone 41.3 parts by mass
[0327] 14.7 parts by mass of tetrahydrofuran
[0328] PKHB solution (solid content 40% by mass) 43.8 parts by mass
[0329] (Gabriel Phenoxies phenoxy resin, Mw 32000)
[0330] * The solution is BYK-370 0.4 parts by mass prepared by dissolving phenoxy resin in tetrahydrofuran
[0331] (BYK Japan Co., Ltd., silicone-based surfactant)
[0332] (Comparative Example 3)
[0333] A laminated film roll was prepared in the same manner as in Example 1 except that the resin sheet was formed so that the maximum cross-sectional height (St) of the surface (1) of the resin sheet opposite to the release layer was 75 nm.
[0334] The base film used in each example was aged at 40° C. for 3 days after the release layer was processed and then used. The obtained laminated film was also aged at 40° C. for 3 days and then evaluated.
[0335] (Example 16)
[0336] A laminated film roll was produced in the same manner as in Example 6 except that the type of resin was changed to resin solution Z8.
[0337] (Resin solution Z8)
[0338] Methyl ethyl ketone 41.3 parts by mass
[0339] 12.3 parts by mass of tetrahydrofuran
[0340] Vylon 200 solution (solid content 30% by mass) 40.8 parts by mass
[0341] (Toyobo Co., Ltd. polyester resin, Mn17000, MEK / toluene solution)
[0342] * The solution is 5.3 parts by mass of Millionate MTL prepared by dissolving polyester resin in MEK / toluene solution
[0343] (Tosoh Corporation, isocyanate crosslinking agent, viscosity 50 mPa·s, solid content 99 mass %)
[0344] BYK-370 0.4 parts by mass
[0345] (BYK Japan Co., Ltd., silicone-based surfactant)
[0346] (Example 17)
[0347] A laminated film roll was produced in the same manner as in Example 6 except that the types of the resin and the cross-linking agent were changed to the resin solution Z9.
[0348] (Resin solution Z9)
[0349] Methyl ethyl ketone 41.3 parts by mass
[0350] 7.4 parts by mass of tetrahydrofuran
[0351] UR-4800 (solid content 32% by mass) 49.2 parts by mass
[0352] (Polyester urethane resin manufactured by Toyobo Co., Ltd., Mn25000, MEK / toluene solution)
[0353] NIKALAC MW-30 1.8 parts by mass
[0354] (Made by Sanwa Chemical Co., Ltd., melamine crosslinking agent, viscosity 1800 mPa·s, solid content 100 mass %)
[0355] BYK-370 0.4 parts by mass
[0356] (BYK Japan Co., Ltd., silicone-based surfactant)
[0357] The compositions, evaluation results, and the like of Examples and Comparative Examples are shown in Table 1A, Table 1B, Table 2A, and Table 2B.
[0358] [Table 1A]
[0359]
[0360] [Table 1B]
[0361]
[0362] [Table 2A]
[0363]
[0364] [Table 2B]
[0365]
[0366] The laminated sheet of the present invention obtained in the embodiment can provide, for example, a resin sheet that can improve transparency in optical applications, and a resin sheet that shows high smoothness. In addition, high smoothness and high sliding properties can be taken into account, for example, scratches can be suppressed in the conveying process, and the reduction of the yield rate can be avoided.
[0367] In addition, it is possible to provide a resin sheet that exhibits high smoothness for electronic component applications such as film capacitor applications, and the resin sheet can improve electrical properties such as dielectric breakdown voltage. In addition, it is possible to achieve both high smoothness and high sliding properties, for example, it is possible to suppress winding misalignment and wrinkles when the dielectric resin sheet is wound on a roll, and it is possible to exhibit good winding properties. Therefore, it is possible to transport the sheet while maintaining excellent capacitor performance.
[0368] Furthermore, the resin sheet obtained in the present invention contains substantially no particles, and thus insufficient transparency such as increased internal haze can be avoided. In addition, the problem of uneven amount of particles transferred to the resin sheet can be avoided, and good sliding properties can be exhibited.
[0369] In contrast, since Comparative Example 1 did not have the release layer of the present invention, the releasability of the resin sheet was extremely poor and the resin sheet could not be evaluated. In Comparative Example 2, since the resin sheet forming composition did not contain a crosslinking agent, the sliding property of the resin sheet was particularly poor.
[0370] In Comparative Example 3, the maximum cross-sectional height (St) of the surface (1) of the resin sheet was out of the range of the present invention, and therefore, the sliding property of the resin sheet was particularly poor.
[0371] Industrial Applicability
[0372] The present invention relates to a laminated film roll on which a resin sheet is laminated, and particularly to a laminated film roll on which a resin sheet used for electronic components or optical applications is laminated.
[0373] Description of Reference Numerals
[0374] 10 Base film
[0375] 11 Release layer
[0376] 12 Resin Sheet
[0377] 13 Surface of resin sheet (1)
[0378] 14. The surface of the resin sheet (2).
Claims
1. A laminated film roll comprising: a polyester-based base film, a release layer disposed on at least one side of the base film, and a resin sheet disposed on a side of the release layer opposite to the base film, The laminated film roll meets the following requirements: The resin sheet is obtained by curing a resin sheet-forming composition containing at least a resin component (A) and a crosslinking agent (B). The resin sheet contains substantially no particles. The film thickness (t1) of the resin sheet is 1 μm or more and 20 μm or less, The arithmetic mean height (Sa) of the surface (1) of the resin sheet on the opposite side to the release layer is 2 nm or more and 30 nm or less, The maximum cross-sectional height (St) of the surface (1) of the resin sheet on the opposite side to the release layer is 80 nm or more and 1000 nm or less, The static friction coefficient measured by overlapping the surface (1) of the resin sheet on the opposite side to the release layer and the surface (2) of the resin sheet on the release layer side is 1.5 or less, The roll hardness of the surface of the laminated film roll is 900 or less.
2. The laminated film roll according to claim 1, wherein: The crosslinking agent (B) contained in the resin sheet forming composition is liquid at 30°C.
3. The laminated film roll according to claim 1, wherein: When the total solid content of the resin sheet is 100% by mass, the ratio of the crosslinking agent (B) contained in the resin sheet to the entire resin sheet is 10% by mass or more.
4. The laminated film roll according to claim 1, wherein: The weight average molecular weight of the resin component (A) contained in the resin sheet is 10,000 or more.
5. The laminated film roll according to claim 1, wherein: The surface free energy of the release layer is 40mJ / m 2 Below, and water adhesion energy is 3.0mJ / m 2 above.
6. The laminated film roll according to claim 1, wherein: The arithmetic mean height (Sa) of the surface on the release layer side of the base film is 20 nm or less, and the maximum protrusion height (P) is 500 nm or less.
7. A method for manufacturing a laminated film roll, characterized in that: The method for producing a laminated film roll according to any one of claims 1 to 6 comprises applying a resin sheet on the release layer and molding the film by a solution film forming method.
Citation Information
Patent Citations
Easily-slidable polyester film, and production process therefor
JP2012144021A
Release film for fuel cell manufacture, laminate, and manufacturing method of fuel cell
JP2014154273A
Polyester film for producing resin film
JP2015182261A
Optical film and method for producing the same, polarizing plate and liquid display device
JP2019095661A
Film capacitor, film for film capacitor, and method for manufacturing film for film capacitor
WO2020039638A1